Mathematical models and immune cell biology - Molina-París, Carmen; Lythe, Grant 1966- (Springer, 2011)
Mathematical immunology is in a period of rapid expansion and excitement. At recent meetings, a common language and research direction has emerged amongst a world-class group of scientists and mathematicians. Mathematical Models and Immune Cell Biology aims to communicate these new ideas to a wider audience. The reader will be exposed to a variety of tools and methods that go hand-in-hand with the immunological processes being modeled. This volume contains chapters, written by immunologists and mathematicians, on thymocytes, on T cell interactions, activation, proliferation and homeostasis, as well as on dendritic cells, B cells and germinal centers. Chapters are devoted to measurement and imaging methods and to HIV and viral infections.